Undernutrition in ART-naïve Nigerian children - Shantakumari N; John LJ; Sreedharan J (International Journal of General Medicine, 2015)
Nisha Shantakumari,1 Lisha Jenny John,2 Jayadevan Sreedharan31Department of Physiology, 2Department of Pharmacology, 3Statistical Support Facility, Centre for Advanced Biomedical Research and Innovation, Gulf Medical University, Ajman, United Arab EmiratesThis letter is a response to the recent paper by Anigilaje and Olutola entitled "Prevalence and risk factors of undernutrition among antiretroviral-therapy-naïve subjects aged under 5 years old in Makurdi, Nigeria: a retrospective study", published in the International Journal of General Medicine.1 The relevance and importance of any sound research on undernutrition in HIV-infected children is high, and we strongly support publication of papers on this topic. However, while we appreciate the health awareness that could be generated by this paper, we have some concerns regarding this study.View the original paper by Anigilaje and Olutola.